Exploring the course-led development of a learning network as a community of practice around a shared interest of rainwater harvesting and conservation agricultural practices: a case study in the Amathole District in the Eastern Cape, South Africa - Weaver, Kim Nichole (Rhodes University, Faculty of Education, Department of Education, 2016)
South Africa has water and food security challenges, especially the Eastern Cape Province where there is a high level of poverty. These challenges place heavy pressure on the agricultural sector as it is the main user of the allocated water in the country. Rainwater harvesting and conservation (RWH&C) practices are explored as a response to these challenges, however information on these practices is not readily available to rural farmers. Agricultural extension has been moving from a top down approach towards a more participatory, collaborative process where what farmers need and want is considered. These participatory approaches need to be explored to enable change in farmer's practice. This research forms part of a Water Resource Commission (WRC) project, Amanzi for Food. (Project K5/2277). The project has the explicit intention of supporting the use of two sets of WRC materials on RWH&C and expanding the learning of these practices through a courseled process within a learning network structure centred around an agricultural college. The network was established with a participatory, applied training of trainer's course that supports and expands knowledge of RWH&C practices amongst network members from different groups within the sector; farmers, trainers, researchers and educators. My main research question was to investigate the process of cultivating a learning network amongst different agricultural actors through a course-led initiative to strengthen the engagement with RWH&C practices. To address this research I used focus group discussions, course observations, participant interviews, participant questionnaires and participant assignment progress to generate data. These data were analysed using Wenger's theory of communities of practice to gauge levels of engagement, participation and learning. Main findings of the study are that the course-led activation of the learning network supported the community of practice members to share their personal experience and achieve social competence in the learning of RWH&C agricultural practices in their context.
Keywords: Uncatalogued